Kdm6a deficiency restricted to mouse hematopoietic cells causes an age- and sex-dependent myelodysplastic syndrome-like phenotype. - Ling Tian (Public Library of Science (PLoS), 2021)
Kdm6a/Utx, a gene on the X chromosome, encodes a histone H3K27me3 demethylase that has an orthologue on the Y chromosome (Uty) (Zheng et al. 2018). We previously identified inactivating mutations of Kdm6a in approximately 50% of mouse acute promyelocytic leukemia samples; however, somatic mutations of KDM6A are more rare in human AML samples, ranging in frequency from 2-15% in different series of patients, where their role in pathogenesis is not yet clear. In this study, we show that female Kdm6aflox/flox mice (with allele inactivation initiated by Vav1-Cre in hematopoietic stem and progenitor cells (HSPCs) have a sex-specific phenotype that emerges with aging, with features resembling a myelodysplastic syndrome (MDS). Female Kdm6a-knockout (KO) mice have an age-dependent expansion of their HSPCs with aberrant self-renewal, but they did not differentiate normally into downstream progeny. These mice became mildly anemic and thrombocytopenic, but did not develop overt leukemia, or die from these cytopenias. ChIP-seq and ATAC-seq studies showed only minor changes in H3K27me3, H3K27ac, H3K4me, H3K4me3 and chromatin accessibility between Kdm6a-WT and Kdm6a-KO mice. Utilizing scRNA-seq, Kdm6a loss was linked to the transcriptional repression of genes that mediate hematopoietic cell fate determination. These data demonstrate that Kdm6a plays an important role in normal hematopoiesis, and that its inactivation may contribute to AML pathogenesis.